DGI-078 Use of SGN35 or Brentuximab Vedotin in Anaplastic Large-Cell Lymphoma: A Case Report in Paediatrics. (12th March 2013) - Joret, P; Siorat, V; Serrano, C; Hochart, C; Brion, F; Storme, T
Abstract : Background: Lymphoma is one of the most frequent haemopathies among children and young adults. Anaplastic large cell lymphoma affects 15% of such children under 15 years old and 40% above 15 years old in France. Although the initial treatments are well codified and the efficacy of chemotherapy is well established in most patients, non-responses or relapses with these drugs are leading haemo-oncologists to look for new and effective therapeutic strategies. Thus, SGN35 or brentuximab vedotin is a monoclonal antibody drug conjugate (mADC). It combines an antibody that selectively targets CD30 expression in tumour cells and a cytotoxic drug derived from auristatin. This cell poison is delivered in situ and leads to apoptotic cell death. SGN35 activity is established in Hodgkin's lymphoma and relapsed or refractory systemic anaplastic large-cell lymphomas that are CD30+. Purpose: To report the use of brentuximab vedotin in a paediatric case study. Materials and Methods: A literature search was undertaken about the use of brentuximab vedotin in paediatrics. The pharmacy undertook the administrative work to obtain the treatment for the patient. Results: In July 2012, FDA licenced this ADC to treat CD30+ Hodgkin's lymphoma and relapsed or refractory systemic anaplastic large-cell lymphoma in adults. It is currently awaiting conditional marketing authorization for adults in Europe. A Phase I/II study in paediatrics is at the moment recruiting. Brentuximab vedotin is administered every three weeks at 1.8 mg/kg (half-life ranges from 4 to 6 days and steady-state was achieved in 21 days for the ADC). Administration is possible in France, after the ANSM granted it temporary authorization on a named patient basis. An 8-year-old male child, with a diagnosis of anaplastic large-cell lymphoma, was treated according to the ALCL99 protocol. Two months after diagnosis the tumour grew under this first-line chemotherapy. A multidisciplinary group decided to start brentuximab vedotin treatment. A total of 5 courses spaced 3-weekly were scheduled combined with chemotherapy. Signs of the tumour disappeared, thorax imaging normalised, fever and pulmonary and mediastinum adenopathies decreased. Conclusions: After the 4th dose of brentuximab vedotin, the treatment was well tolerated by the patient and the tumour regressed. Among adults, the median response is about 12 months. Thus, confirmation of efficacy still has to be evaluated. Further studies are required to establish the efficacy and safety profile in the paediatric population. No conflict of interest.